Decision Support System Pemilihan Supplier Pada Perusahaan Konveksi Menggunakan Metode Fuzzy Analitycal Hierarchy Process (FAHP) - Khasanah, Naim Munah; Farahdiansari, Ardana Putri; Abryandoko, Eko Wahyu (Universitas Muria Kudus, 2024)
Abstrak The success of an industry is influenced by the selection of suppliers and effective evaluation processes. Mistakes in choosing raw material suppliers will affect a company's productivity decline. This research is important to be conducted to identify alternative supplier selections. Convection Yani is an industry engaged in clothing production. The issue at hand is that the thread quality from suppliers tends to differ, thus affecting the quality of the clothing production. The importance of supplier selection can support the provision of quality materials. The purpose of this research is to determine quality thread suppliers by considering multiple criteria using the Fuzzy Analytical Hierarchy Process (FAHP). The criteria considerations involve four criteria: price, quality, delivery, and service. The FAHP method yields the highest values with Toko Rizqi having a weight of 1.00, UD. Sandra with a weight of 0.547, Toko Sumber Baru with a weight of 0.168, and Toko Gloria with a weight of 0.045.